Developing evidence-based design guidelines for medical/ surgical hospital patient rooms that meet the needs of staff, patients, and visitors - Lavender, Steven A.; Radin Umar, Zaid @ Radin Zaid; Sommerich, Carolyn M.; Li, Jing; Sanders, Elizabeth B.N.; Evans, Kevin D.; Patterson, Emily S. (SAGE Publications Inc., 2020)
Objectives: This research investigated medical/surgical (Med/Surg) patient room design to accommodate the needs of hospital staff, while at the same time accommodating the needs of patients and their visitors. Background: Designing hospital patient rooms that provide a comfortable healing experience for patients, while at the same time meeting the needs of the hospital staff, is a challenging process. Prior research has shown that many hospital patient room designs adversely affect the ability of hospital staff to perform their tasks effectively, efficiently, and safely. Method: Twenty-seven design sessions were conducted in which 104 participants, representing 24 different occupations, worked in small mixed occupational groups to design an ideal single patient Med/Surg patient room to fit their collective needs using a full-scale mock-up. During analysis, the investigators reduced the resulting 27 room designs to 5 hybrid designs that were sequentially reviewed by patients and visitors and by staff to address design conflicts. Results: This design process identified 51 desirable room design features that were incorporated into 66 evidence-based design guidelines for the different areas within the Med/Surg patient room including the entry way (16 guidelines), the patient clinical area (22 guidelines), the bathroom (17 guidelines), the family area (8 guidelines), and storage areas for patients and their visitors (3 guidelines). Conclusions: The guidelines developed through this study identified many opportunities for improving the design of hospital Med/Surg rooms to allow staff to be more effective, efficient, and safer, while at the same time addressing the design needs of patients and their visitors.